No evidence for induction or selection of mutant sodium channel expression in the copepod Acartia husdsonica challenged with the toxic dinoflagellate Alexandrium fundyense. Issue 17 (22nd August 2014) - Finiguerra, Michael; Avery, David E.; Dam, Hans G.
Abstract Some species in the dinoflagellate genus Alexandrium spp. produce a suite of neurotoxins that block sodium channels, known as paralytic shellfish toxins (PST), which have deleterious effects on grazers. Populations of the ubiquitous copepod grazer Acartia hudsonica that have co‐occurred with toxic Alexandrium spp. are better adapted than naïve populations. The mechanism of adaptation is currently unknown. We hypothesized that a mutation in the sodium channel could account for the grazer adaptation. We tested two hypotheses: (1) Expression of the mutant sodium channel could be induced by exposure to toxic Alexandrium fundyense; (2) in the absence of induction, selection exerted by toxic A. fundyense would favor copepods that predominantly express the mutant isoform. In the copepod A. hudsonica, both isoforms are expressed in all individuals in varying proportions. Thus, in addition to comparing expression ratios of wild‐type to mutant isoforms for individual copepods, we also partitioned copepods into three groups: those that predominantly express the mutant (PMI) isoform, the wild‐type (PWI) isoform, or both isoforms approximately equally (EI). There were no differences in isoform expression between individuals that were fed toxic and nontoxic food after three and 6 days; induction of mutant isoform expression did not occur. Furthermore, the hypothesis that mutant isoform expression responds to toxic food was also rejected. That is, no consistent evidence showed that the wild‐type to mutant isoform ratios decreased, or that the relative proportion of PMI individuals increased, due to the consumption of toxic food over four generations. However, in the selected line that was continuously exposed to toxic food sources, egg production rate increased, which suggested that adaptation occurred but was unrelated to sodium channel isoform expression.